Continuous boundary condition at the interface for two coupled fluids. (January 2023) - Legeais, François; Lewandowski, Roger
Abstract: We consider two laminar incompressible flows coupled by the continuous law at a fixed interface Γ I . We approach the system by one that satisfies a friction Navier law at Γ I, and we show that when the friction coefficient goes to ∞, the solutions converge to a solution of the initial system. We then write a numerical Schwarz-like coupling algorithm and run 2D-simulations, that yields same convergence result.